2018
DOI: 10.3390/ijerph15020283
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms of Chinese Children: Prevalence and Correlated Factors among Subgroups

Abstract: Economic growth and socioeconomic changes have transformed nearly every aspect of childhood in China, and many are worried by the increasing prevalence of mental health issues among children, particularly depression. To provide insight into the distribution of depressive symptoms among children in China and identify vulnerable groups, we use data from the 2012 China Family Panel Survey (CFPS), a survey that collected data from a large, nationally representative sample of the Chinese population. Using the CFPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
2
38
4
Order By: Relevance
“…The rates of depression symptoms (20.9% for junior high school students and 29.7% for high school students) and anxiety symptoms (25.4% for junior high school students and 28.4% for high school students) were higher than the rates reported by recent studies that did not involve any epidemic or pandemic. For instance, a recent study was conducted with a sample of 2,679 children aged 10–15 years old from 25 provinces in China, and the results revealed that the rates of depressive symptoms are significantly lower in urban areas (14%) than in rural areas (23%) [ 31 ]. Another study surveyed 1,597 junior high school students aged 10–17 years in Shang Hai City (an urban area in China), and the results showed that the rates of anxious symptoms and depressive symptoms were 16.4%and 17.2%, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of depression symptoms (20.9% for junior high school students and 29.7% for high school students) and anxiety symptoms (25.4% for junior high school students and 28.4% for high school students) were higher than the rates reported by recent studies that did not involve any epidemic or pandemic. For instance, a recent study was conducted with a sample of 2,679 children aged 10–15 years old from 25 provinces in China, and the results revealed that the rates of depressive symptoms are significantly lower in urban areas (14%) than in rural areas (23%) [ 31 ]. Another study surveyed 1,597 junior high school students aged 10–17 years in Shang Hai City (an urban area in China), and the results showed that the rates of anxious symptoms and depressive symptoms were 16.4%and 17.2%, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression was assessed using the Chinese version of the Center for Epidemiologic Studies Depression Scale. CES-D has been widely used in Chinese adolescents, with good reliability and validity [14,44]. CES-D consists of 20 items, each of which being answered on a four-point scale (0 = rarely or none of the time, 1 = some or a little of the time, 2 = moderately or much of the time, and 3 = most or all of the time), including four dimensions: negative affect (8 items), positive affect (4 items), somatic symptoms and retarded activity (6 items), and interpersonal difficulties (2 items).…”
Section: Depressionmentioning
confidence: 99%
“…As for mainland China, researchers have found that Chinese teenagers are also at a high risk of developing depressive symptoms. For example, Zhou et al [14] have found depressive symptoms ranging 14% in urban areas to 23% in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…In one province sample of China, 25% of all children display symptoms of depression [ 1 ]. Other research has shown that, in 2012, 20.3% of Chinese children aged 10–15 years displayed symptoms of depression, and this share was even higher among Chinese children from rural areas (23%) [ 2 ]. According to the 6th national census, there are 39.20 million children in rural areas, which means nearly 9.02 million rural children display symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%